THE RISE OF THE BEAUTY INDUSTRY IN INDONESIA: ASSESSING ITS CONTRIBUTION TO NATIONAL ECONOMIC GROWTH - Saparuddin Saparuddin; Alifah Kusumaningrum; Amanda Setiorini; Erika Takidah (Adisam Publisher, 2025)
The beauty industry in Indonesia has shown very dynamic and resilient growth, especially in the last five to ten years. The surge in demand for skincare products, cosmetics, and beauty services has been driven by the digitalization trend, changes in consumer lifestyles, and increasing public awareness of skin appearance and health. This study aims to estimate the contribution of the beauty industry to national economic growth using the literature review method. This approach involves a critical review of various secondary sources, including data from the Central Statistics Agency, industry reports from the Ministry of Industry, academic studies, and publications from beauty industry associations. The results of the study show that this industry has a broad economic impact, not only through direct contributions to Gross Domestic Product, but also through job creation, increased MSME activity, strengthening local supply chains, and the development of the digital sector. The beauty industry also plays a role in increasing local product exports and strengthening cultural identity through products based on natural Indonesian ingredients. This study emphasizes the need for a targeted national strategy to optimize the potential of the beauty sector as one of the motors of creative economic growth, as well as part of a sustainable and inclusive economic transformation.